Synthesis and characterization NS-reduced graphene oxide hydrogel and its electrochemical properties - Nugroho A.; Erviansyah F.; Floresyona D.; Mahalingam S.; Manap A.; Afandi N.; Lau K.S.; Chia C.H. (Institute for Metals Superplasticity Problems of Russian Academy of Sciences, 2023)
Developing materials with good electrochemical performance is critical in energy storage applications. One of the promising materials for these applications is reduced graphene oxide (rGO) based materials. Utilizing thiourea as a nitrogen (N) and sulfur (S) source, we present a simple hydrothermal approach for simultaneous doping of nitrogen and sulfur into the rGO hydrogel structure. The visual photograph shows the hydrogel form of the sample. XRD and Raman analysis shows the carbon structural changes during the reduction process. The presence of N and S atoms which spread evenly on the hydrogel structure, was confirmed by energy-dispersive x-ray (EDX) mapping. A cyclic voltammetry measurement at a current density of 0.5 A / g reveals that the NS-rGOH sample has a high specific capacity of 750 C / g. Even at a current density of 10 A / g, it can maintain outstanding charge-discharge stability, with 83.3 % of the initial capacity preserved after 1000 charge-discharge cycles. Moreover, EIS analysis reveals that the low charge transfer resistance and high ionic diffusivity of the rGO hydrogel sample lead to good electrochemical performance. NS doping into the rGOH structure improves the sample's electrochemical performance compared to the undoped sample. 2022, Institute for Metals Superplasticity Problems of Russian Academy of Sciences. All rights reserved.